Desenvolvimento e validação de um instrumento para triagem em cirurgias de urgência - Torezan, Stéfany Vareschi (2024)
Introduction: The increase in life expectancy among the population has been accompanied by a significant growth in demand for emergency surgical care, due to the high incidence of acute episodes of chronic diseases, traumas from traffic accidents, and urban violence. Emergency surgeries are medical procedures that must be performed as soon as possible to save the patient's life. However, not all cases are considered emergencies, and often patients with less severe health problems end up being referred for these procedures, increasing the waiting time for truly serious cases. Objective: To develop and validate a screening tool that can be used by healthcare professionals to identify cases requiring emergency surgery. Method: This was a methodological research with a descriptive design and quantitative approach, conducted at the Teaching Hospital of Northern Paraná. It was conducted in three distinct stages: identification of the state of the art, production, and validation of the proposed instrument. An integrative literature review was performed to identify gaps and opportunities for the development of the instrument to screen patients for emergency surgeries. Considering the predominance of care in these areas in the institution, experienced surgeons specializing in emergency care, with a minimum specialization in General Surgery, Orthopedics, Vascular Surgery, Urology, and Neurosurgery, evaluated, through forms with response scales about the importance of each item, using the Delphi technique for validation. The Content Validation Coefficient (CVC) was calculated for each item on the scale based on the proportion of specialists who classified it as valid (important or very important), defining a consensus index of 90% for items related to clinical parameters common to all specialties and 100% for specific ones. Thus, a classification instrument for emergency surgeries is proposed in the hospital context. Results: 25 doctors were consulted, and 13 specialists responded to the questionnaires (response rate of 52%). Predominantly male (84.62%), aged between 28 and 57 years old, with experience ranging from 5 to 32 years, most of them work in public institutions. The Content Validity Index (CVI) revealed a 90% agreement among specialists, although certain specialties invalidated some items. Based on these results, this instrument aimed at optimizing this specific care in the operating room was developed. Conclusion: The instrument resulting from this study suggests to be a valuable contribution to clinical practice, providing a more efficient approach in this specific classification.